The Concept of Tradition in the Catholic Theology of the Second Vatican Council: Kongar’s Analytical Approach - Матић, Златко (Sabornost - The Theological Year-book, 2013)
Theology of Tradition is one of the most important topics of theological research of Yves Congar. In order o fully understand the significance, originality and creative innovation of his theological conclusions on the subject of the Holy Tradition, it is necessary to take seriously into account the situation and ecclesiological climate that housed the Roman Catholic Church in the first half of the XX century, all up until the great milestone — the Second Vatican Council (1962–1965). Historical development of understanding the category of Tradition before the Council, must be well studied, because the indications of this theologian quickly turned into the legacy of the Catholic Church and were unanimously accepted as “traditional”, so that today, at some point, they have lost on exclusivity, uniqueness and importance, which were adorned in the most important moment.